Evidences for a Role of Gut Microbiota in Pathogenesis and Management of Epilepsy - Amlerova, Jana; Šroubek, Jan; Angelucci, Francesco; Hort, Jakub (International journal of molecular sciences, 2021)
Epilepsy as a chronic neurological disorder is characterized by recurrent, unprovoked epileptic seizures. In about half of the people who suffer from epilepsy, the root cause of the disorder is unknown. In the other cases, different factors can cause the onset of epilepsy. In recent years, the role of gut microbiota has been recognized in many neurological disorders, including epilepsy. These data are based on studies of the gut microbiota-brain axis, a relationship starting by a dysbiosis followed by an alteration of brain functions. Interestingly, epileptic patients may show signs of dysbiosis, therefore the normalization of the gut microbiota may lead to improvement of epilepsy and to greater efficacy of anticonvulsant drugs. In this descriptive review, we analyze the evidences for the role of gut microbiota in epilepsy and hypothesize a mechanism of action of these microorganisms in the pathogenesis and treatment of the disease. Human studies revealed an increased prevalence of Firmicutes in patients with refractory epilepsy. Exposure to various compounds can change microbiota composition, decreasing or exacerbating epileptic seizures. These include antibiotics, epileptic drugs, probiotics and ketogenic diet. Finally, we hypothesize that physical activity may play a role in epilepsy through the modulation of the gut microbiota.
Keywords: Firmicutes; Brain; dysbióza; epilepsy; treatment; ketogenic diet; mozek; Epilepsy; Humans; střevní mikroflóra; gut microbiota; physical activity; epilepsie; Dysbiosis; Gastrointestinal Microbiome; lidé